PROPERTY TAX REFORM AND CONTROVERSIAL POLITICS: MEDIA NARRATIVES AND THE ESCALE OF PROTESTS IN BONE - Anan Dita Asrawati; Irma Suryani Arfah; Syahrir; Hadisaputra (Jurnal Sosiologi Dialektika Sosial, 2026)
Local property tax reforms are increasingly promoted to strengthen fiscal autonomy in developing contexts, yet sharp tax increases often trigger community resistance when perceived as unfair and poorly communicated. This article examines the protest episode surrounding the PBB-P2 increase in Bone Regency, Indonesia, focusing on how structural conditions and mediated narratives shaped collective resistance. This research uses a qualitative case study design based on document and media text analysis, utilizing thematic, narrative, and media discourse analysis to trace the escalation pathways and the configuration of the actors involved. The results show that resistance developed incrementally, moving from public complaints to an organized protest peak on 13 August 2025. Farmers and small traders emerged as central actors, articulating economic vulnerability and fiscal injustice, while students functioned as brokers that amplified mobilization and legitimacy. The absence of effective socialization and the regent’s limited direct engagement contributed to a legitimacy deficit, accelerating escalation and disorder. These findings suggest that local taxation disputes become contentious politics when economic strain, perceived distributive injustice, and weak accountability mechanisms converge.